Risks related to the lack of lubrication on surface integrity in drilling. Issue 1 (January 2019) - Girinon, Mathieu; Karaouni, Habib; Masciantonio, Ugo; Lefebvre, Fabien; Jourden, Erwan; Valiorgue, Frédéric; Rech, Joël; Feulvarch, Eric
Abstract: Drilling processes can significantly affect the surface integrity of metallic components. Thus, the control of the drilling process is of great interest for industry to ensure a satisfactory surface behavior. The understanding of such a process is complex because the hole is confined. Therefore, the physical phenomena are not easily observable during a drilling operation. The aim of this article is to present an experimental investigation on the effect of the drilling conditions for the machining of an austenitic stainless steel 316L. Three cases of lubrication are studied: internal coolant, external coolant and dry. The objective is to identify the mechanical and thermal contributions on surface integrity. In this study, the influence of the lubrication conditions is first characterized during the drilling operation (temperatures around the drilled surface, forces…). Then, the effect of lubrication on the surface integrity after drilling is clearly highlighted by analyzing the hole diameters, the drill deflections, the roughness, the residual stresses, the hardness and the microstructure.